The Impact of Environmental Factors on Ecological Balance and the Bioactive Complexity of the Mangrove Avicennia alba in the Youtefa Bay Nature Tourism Area (YBNTA), Jayapura City - Wambrauw, Daniel Z. K.; Tuhumena, Lolita; Numberi, Yulindra M.; Mishbach, Imam; Suharno, Suharno; Runtuboi, Dirk Y.P. (Jurnal Biologi Papua, 2025)
The natural tourism area of Teluk Youtefa in Jayapura City is known for its mangrove forests, rich in biodiversity, particularly Avicennia alba. Mangroves serve as coastal buffers, pollutant filters, and habitats for various flora and fauna. However, climate change, pollution, and human activities can affect the ecological balance and bioactive compound content of A. alba, which has long been recognized as a potential source of medicinal and natural antioxidant compounds. Fluctuations in water quality, invasive species, and land-use changes may disrupt both the ecosystem and the complexity of its bioactive constituents. Understanding the impact of environmental factors on both aspects is crucial for effective and sustainable conservation. This study aims to explore the relationship between environmental factors and the production of bioactive compounds in mangroves. The research investigates how environmental changes influence the ecological balance and bioactive content of Avicennia alba, and their implications for the sustainability of the Teluk Youtefa mangrove tourism area. Sampling was conducted using a purposive sampling method, focusing on environmental parameters such as temperature, salinity, pH, dissolved oxygen (DO), biological oxygen demand (BOD), and total suspended solids (TSS), along with laboratory analysis of bioactive compounds. The results show that the site with poor environmental quality (Site 1) recorded DO at 3.2 mg/L, BOD at 5.8 mg/L, and Pb at 0.07 mg/L. In contrast, the site with better environmental conditions (Site 3) showed DO at 5.5 mg/L, BOD at 2.1 mg/L, and salinity at 32.4 ppt. The bioactive compounds identified include Wagner’s alkaloids, Dragendorff’s alkaloids, flavonoids, terpenoids, saponins, and tannins. The polluted site (Site 1) yielded only three compounds—flavonoids, terpenoids, and saponins—whereas the conservation site (Site 3) revealed the full set of six bioactive compounds, including alkaloids and tannins. These findings indicate that environmental quality has a direct influence on the complexity of bioactive compounds and the ecological potential of mangrove ecosystems.